Penyebab Maraknya Pengangguran Lulusan Perguruan Tinggi Di Indonesia - Haris, Abdul (Jurnal Manajemen dan Bisnis (JMB), 2025)
Unemployment among college graduates in Indonesia is a crucial issue in the economic field, especially because the high number of graduate unemployment indicates an imbalance between the growth of the educated workforce and the needs of the labor market. This phenomenon can be caused by various factors, such as the mismatch of skills with industry needs, slow economic growth, and the imbalance between the number of graduates and available jobs. Therefore, this study aims to examine the economic factors that are the main causes of the high unemployment among college graduates in Indonesia using a literature study approach. This research was conducted using a qualitative method with a library research approach, where data were collected from various academic literature, official reports, and relevant previous research. Data sources include scientific journals, books, reports from government agencies such as the Central Statistics Agency (BPS), and publications from international organizations. Data analysis was carried out by reviewing previous theories and findings to identify economic patterns and factors that contribute to the unemployment rate of college graduates. The results of this study are expected to provide a more comprehensive understanding of the root causes of unemployment among college graduates from an economic perspective. In addition, this study aims to provide recommendations based on theoretical studies for policy makers in designing strategies to improve the quality of the workforce and more effective economic policies to reduce the number of graduate unemployment in Indonesia.